An investigative study on discrimination of honey of various floral and geographical origins using UPLC-QToF MS and multivariate data analysis. (February 2017) - Jandrić, Z.; Frew, R.D.; Fernandez-Cedi, L.N.; Cannavan, A.
Abstract: An untargeted metabolomics approach was applied for the discrimination of honey of various floral and geographical origins using ultra-performance liquid chromatography-quadrupole time of flight mass spectrometry (UPLC-QToF MS). Evaluation of data by multivariate data analysis allowed the discrimination of New Zealand and Australian honeys from honeys originating in other countries. It was also possible to differentiate between mono- and polyfloral honeys within one region, as well as between some monofloral honeys of various geographical origins. Characteristic markers, contributing to the segregation of different honey types, were selected and characterized. Highlights: Analysis of honey of various floral and geographical origins. Discrimination was achieved using UPLC-QToF MS and multivariate data analysis. Differentiation was obtained between uni- and polyfloral honeys within one region. Some unifloral honeys of various geographical origins were differentiated. Characteristic markers, contributing to the segregation, were characterized.